Live table fish transportation - a means of innovative value addition in the fish retail markets of Ludhiana, Punjab - Muzaddadi, A. U.; Ahmad, T.; Monika, Monika; Nanda, S. K. (Indian Journal of Fisheries, 2018)
In the present study, different means of transportation of live table fish in Sherpur Fish Market, Ludhiana District in Punjab were investigated. Two methods, one for short distance (travel time <2h) and the other for long distance transportation (travel time 2-6 h), were studied. The transportation method for short distance was with tricycle-rickshaw either pulled by humans or by a moped, wherein, a wooden cuboid (1.5x1.0x1.0 m) with internal polythene lining was used with a carrying capacity of 50-100 kg fish. In the long distance transportation method, polythene lined truck-pool of 3.1x1.83x0.75 m was used and about 600-700 kg fish per truck-pool was transported. About 50 to 100% fish mortality was observed in the long-distancecarriage or truck-pool method, whereas, only 10- 20% mortality was recorded in short-distance-carriage or cart method. The fish transported were primarily carps weighing 300-1500 g each and comprised catla (catla catla ), rohu (Labeo rohita), mrigal (Cirrhinus mrigala), common carp (Cyprinus carpio), big-head carp (Hypophthalmichthys nobilis) and silver carp (Hypophthalmichthys molitrix). The live fish packaging and transportation were used as a means of value addition to ensure fresh quality and added market price per unit fish. The retail price of live table carps ranged from `120-200 kg-1 based on species of fish and its size, whereas, the dead and iced fish was priced below `100 kg-1. The major problems faced in live fish transportation were lack of aeration of water during transportation, inconvenient and cumbersome nature of existing method and accident proneness. The study suggested the need for scientific intervention in mainly two aspects such as 1) to develop a handy method of live table fish transportation compatible to truck-pools and 2) to develop an aerator appropriate for the live-fish transportation containers in order to overcome the existing problems.